Labelled transition system approach to distributed computing systems - Hung, Dang Van (Journal of Computer Science and Cybernetics, 2016)
The present paper introduces the  notion of  distributed transition systems for modeling, designing and  understanding distributed computing systems. The concurrency can be expressed explicitly in the model. Some of  the  global properties of the  systems are discussed and determined. It is  shown in the paper that  by keeping knowledge of other processes in each process of a system, some of its global properties can be synthesized from only few local process states.